Dual-Functional Polymeric Micelles Co-Loaded with Antineoplastic Drugs and Tyrosine Kinase Inhibitor for Combination Therapy in Colorectal Cancer - Ying-Hsia Shih; Cheng-Liang Peng; Ping-Fang Chiang; Ming-Jium Shieh (MDPI AG, 2022)
The aim of this research was to evaluate the receptor tyrosine kinase inhibitor Sunitinib combined with SN-38 in polymeric micelles for antitumor efficacy in colorectal cancer. First, SN-38 and Sunitinib co-loaded micelles were developed and characterized. We studied cell viability and cellular uptake in HCT-116 cells. Then, subcutaneous HCT-116 xenograft tumors were used for ex vivo biodistribution, antitumor efficacy, and histochemical analysis studies. Results of cellular uptake and ex vivo biodistribution of SN-38/Sunitinib micelles showed the highest accumulation in tumors compared with other normal organs. In the antitumor effect studies, mice bearing HCT-116 tumors were smallest at day 28 after injection of SN-38/Sunitinib micelles, compared with other experiment groups (p < 0.01). As demonstrated by the results of inhibition on multi-receptors by Sunitinib, we confirmed that SN-38/Sunitinib co-loaded micelles to be a treatment modality that could inhibit VEGF and PDGF receptors and enhance the antitumor effect of SN-38 (p < 0.05). In summary, we consider that this micelle is a potential formulation for the combination of SN-38 and Sunitinib in the treatment of colorectal cancer.